Attenuation of quorum sensing mediated virulence factors production and biofilm formation in Pseudomonas aeruginosa PAO1 by Colletotrichum gloeosporioides HM3. (February 2021) - Meena, Himani; Mishra, Rashmi; Ranganathan, Sampathkumar; Sarma, V. Venkateswara; Ampasala, Dinakara Rao; Siddhardha, Busi
Abstract: Signal dependent microbial communication in Pseudomonas aeruginosa PAO1 is a typical phenomenon mediated by acyl homo-serine lactone molecules that helps in developing biofilm and enhance antibiotic resistance. Microbial sources provide insight to the hidden treasure of secondary metabolites, and these structurally diversified chemical motifs can be used as antimicrobial and anti-infective agents. In the present study, endophytic fungus, Colletotrichum gloeosporioides HM3 isolated from Carica papaya leaves was explored for anti-infective potential against P. aeruginosa PAO1. The crude extract of C. gloeosporioides HM3 displayed bacteriostatic effect on P. aeruginosa PAO1 growth at 750 μg/ml concentration. A significant decline was observed in the production of quorum sensing regulated virulence factors, i.e. 56.32%, 62.54%, and 66.67% of pyocyanin, chitinase, and elastase enzyme, respectively. A drastic reduction in pathogenic determinant behaviour after treatment with crude extract of C. gloeosporioides HM3 i.e. EPS, rhamnolipid, and HCN production was noted. Light microscopy and CLSM analysis revealed that fungal extract treatment has reduced bacterial ability to form dense biofilm architecture. In silico analysis demonstrated the binding efficiency of bioactive compound, 4-(2, 3-dimethoxybenzylidene)-3-methyl-1-(4-nitrophenyl)-2-pyrazolin-5-one, which is equipotent to the natural ligand and displayed a docking score of −5.436 kcal/mol with QS transcriptional regulator (LasR). Whereas the compound Acetamide, n-[tetrahydro-3-(phenylmethyl) thieno [3, 4-d]thiazol-2 (3 h)-ylidene]-, s, s-dioxide exhibits a docking score of −4.088 kcal/mol (LasR) and −1.868 kcal/mol (RhlR) with cognate receptor proteins. Henceforth, the research report suggests C. gloeosporioides HM3 derived metabolites could be considered as a potential inhibitors of QS regulated virulence factors and biofilm production in P. aeruginosa PAO1. Graphical abstract: Image 1 Highlights: Indiscriminate use of conventional drugs led to antibiotic resistance in microorganisms. Pseudomonas aeruginosa triggers virulence factors production via the quorum-sensing system. Colletotricum gleosporioides exhibits a bacteriostatic effect and impedes the QS-governed pathogenic determinants in P. aeruginosa. Molecular docking, results showed the interaction of bioactive molecule, DNP with LasR and RhlR receptors of P. aeruginosa. Bioactive metabolites identified in the crude extract can be further exploited for anti-infective potential.